2021
DOI: 10.3164/jcbn.19-130
|View full text |Cite
|
Sign up to set email alerts
|

Endosonographic features in patients with non-alcoholic early chronic pancreatitis improved with treatment at one year follow up

Abstract: Since the prevention of early chronic pancreatitis (ECP) into chronic pancreatitis might be critical for the reduction of pancreatic cancer, we tried to clarify the pathophysiology of ECP patients, focusing on ECP patients without alcoholic chronic pancreatitis. 27 ECP patients without alcoholic chronic pancreatitis and 33 patients with functional dyspepsia with pancreatic enzyme abnormalities (FD-P) were enrolled in this study. Diagnosis of ECP was made when imaging findings showed the presence of more than 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…We have also reported that the elevation of duodenal inflammatory responses including GLP-1 producing cells expression in FD-P patients and exocrine pancreatic insufficiency has been also reported to be affected by gut hormones such as GLP-1. (4,10,(25)(26)(27) Further studies will be needed to clarify how the exocrine pancreatic insufficiency may associate with the pathophysiology of FD patients including the disturbance of physical quality of life through duodenal inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also reported that the elevation of duodenal inflammatory responses including GLP-1 producing cells expression in FD-P patients and exocrine pancreatic insufficiency has been also reported to be affected by gut hormones such as GLP-1. (4,10,(25)(26)(27) Further studies will be needed to clarify how the exocrine pancreatic insufficiency may associate with the pathophysiology of FD patients including the disturbance of physical quality of life through duodenal inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…(4,5,8,9) In addition, previous studies and our data have reported that endosonography can reveal abnormalities in pancreas in patients with persistent dyspepsia. (3)(4)(5)10) Therefore, in this study, we compared clinical characteristics and exocrine pancreatic function in FD patients with pancreatic enzyme abnormalities with those in asymptomatic patients with pancreatic enzyme abnormalities. We analyzed the prevalence of exocrine pancreatic insufficiency in FD patients with pancreatic enzyme abnormalities to clarify whether the pathophysiology of FD patients including clinical symptoms and quality of life were associated with exocrine pancreatic insufficiency.…”
mentioning
confidence: 99%
“…Considering of Ishikura's study, camostat mesilate may improve pancreatic pain through the inhibition of neuronal activation. In addition, we have reported the treatment including camostat mesilate improved EUS findings in one year-follow up study 26 . Further studies will be needed to clarify why camostat mesilate can improve EUS findings in ECP patients.…”
Section: Association Between Pancreatic Dysfunction and The Duodenum (1)decreased Pancreatic Bicarbonate Secretion In The Duodenummentioning
confidence: 76%
“…Gut hormones secreted from the duodenal mucosa, including GLP-1, GIP, and PYY have been shown to play critical roles in gastric motility and the absorption of nutrients [23][24][25] . To clarify the differences in duodenal inflammatory responses between functional dyspepsia with pancreatic enzyme abnormalities (FD-P) patients and ECP patients, we compared various phenotypes of duodenal inflammatory cells such as GLP-1positive cells and degranulated eosinophils between FD-P patients and ECP patients 8,26 .…”
Section: Duodenal Inflammation Plays Pivotal Roles In Fd Patientsmentioning
confidence: 99%
See 1 more Smart Citation